2004
DOI: 10.1097/01.asn.0000130565.69170.85
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in Connective Tissue Growth Factor by Antisense Treatment Ameliorates Renal Tubulointerstitial Fibrosis

Abstract: Abstract. Connective tissue growth factor (CTGF/CCN2) is one of the candidate factors mediating fibrogenic activity of TGF-␤. It was shown previously that the blockade of CTGF by antisense oligonucleotide (ODN) inhibits TGF-␤-induced production of fibronectin and type I collagen in cultured renal fibroblasts. The in vivo contribution of CTGF in renal interstitial fibrosis, however, remains to be clarified. With the use of a hydrodynamics-based gene transfer technique, the effects of CTGF antisense ODN are inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
210
3
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(225 citation statements)
references
References 51 publications
10
210
3
2
Order By: Relevance
“…2,12 Antagonists of CCN2 have proven effective in blocking profibrogenic CCN2 signaling pathways in vitro and have yielded promising data with respect to preventing experimental fibrosis. 14 Regarding renal diseases, knockdown of CCN2 gene expression with antisense gene transfer into rat kidney ameliorates tubulointerstitial fibrosis in obstructive nephropathy 14 and in experimental mice diabetes in C57BL/6 mice. 16 CCN2 is known to function downstream of TGF-b, driving extracellular matrix accumulation and fibrosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,12 Antagonists of CCN2 have proven effective in blocking profibrogenic CCN2 signaling pathways in vitro and have yielded promising data with respect to preventing experimental fibrosis. 14 Regarding renal diseases, knockdown of CCN2 gene expression with antisense gene transfer into rat kidney ameliorates tubulointerstitial fibrosis in obstructive nephropathy 14 and in experimental mice diabetes in C57BL/6 mice. 16 CCN2 is known to function downstream of TGF-b, driving extracellular matrix accumulation and fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…2,12 The concept of CCN2 as a downstream mediator of profibrotic factors, including transforming growth factor-b (TGF-b) and Angiotensin II, is the chief operating paradigm in the field. 13,14 Therapeutic approaches that selectively block endogenous CCN2 activity have proven beneficial effects in fibrotic-related diseases, including experimental lung, liver, vascular, and renal diseases, and some authors have suggested that CCN2 could be a therapeutic target for fibrosis. [12][13][14][15][16] However, cardiac CCN2 overexpression conferred cardioprotection in Angiotensin II-infused mice and in ischemia-reperfusion injury, 17,18 showing that CCN2 exerts protective effects in some pathological settings.…”
mentioning
confidence: 99%
“…Overnight microalbumin (nephelometry)/Cr ratios (mg/g) (mean ϮSD) at days 0 (baseline), 56 (2 weeks after final infusion), and 84 (during washout period) (efficacy population) primarily in podocytes, (6) and the development of more severe DKD in mice overexpressing CTGF specifically in podocytes (47). Heterozygous CTGF knockout (Ϯ) mice developed less severe albuminuria and glomerular basement membrane thickening with diabetes (48), and a CTGF antisense oligonucleotide decreased albuminuria, mesangial hypertrophy, and the increased serum Cr in murine models (streptozotocin and db/db) of type 1 and 2 diabetes (49).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Yokoi et al (35) used antisense ODN technology to demonstrate that CTGF expression in interstitial cells played an important role in interstitial fibrogenesis in the unilateral ureteral obstruction model. Their findings, coupled with ours, support the notion that CTGF acts as an important profibrotic mediator of TGF-␤'s effects in the renal tubulointerstitium while not eliminating the possibility that it plays a similar role in the glomerulus.…”
Section: Discussionmentioning
confidence: 99%